Prevalence of Bullying in Undergraduate Students at a Medical College of Nepal - Singh Bhandari, Mukta; Chataut, Jagdish (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Bullying is a common problem affecting physical and mental health as well as academic performance of students. It also results in harmful coping behaviours like indulgence in alcohol, drug abuse and college drop out. Compared to students from other streams, the proportion of bullying among medical students is very high. The objective of this study was to determine the prevalence of bullying among students in a medical college of Nepal. Methods A cross-sectional study was carried out amongst students of Kathmandu University School of Medical Sciences, enrolled in MBBS stream during the period of September 2021 to July 2022. Ethical approval was taken from Institutional review committee of the institute (Approval number: 76/2021). A semi-structured, self-administered questionnaire was used. Descriptive statistics were performed and Chi-square Test was done. Results The prevalence of bullying in this study was 78% (203) and 145 (71%) of the victims were male. Verbal bullying by classmates and others was 153 (75%) while non-verbal bullying by teacher/ instructor was 120 (59%). Only 50 (24%) had ever complained about bullying and out of 50 complains, 27 (54%) said action was taken but bullying didn't stop in 33 (66%) of the cases. Out of 156 students who didn't complain, 57 (37%) students felt that it was not a big issue. Conclusions Bullying is a very common problem among medical students however most of the students take it lightly and no action is taken after complaining. Thus, students should be made aware about bullying and serious action should be taken against it.